2019
DOI: 10.14740/jnr509
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines in Parkinson’s Disease: Their Role in Oxidative Stress Induction and Protein Aggregation

Abstract: Parkinson's disease (PD) is a systemic neurodegenerative disease characterized by tremor, rigidity, bradykinesia, and stooping posture. When more than 60% of dopaminergic neurons in the substantia nigra of the brain have died, motor symptoms manifest in PD. Currently, oxidative stress (OS) is considered to be one of the leading factors provoking death of dopaminergic neurons in PD. This review is concerned with the role of polyamines in PD, especially focusing on their role in OS induction. Polyamines (putresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 78 publications
3
37
0
Order By: Relevance
“…6A,B). Altered polyamine 23 and phospholipids 24 levels have been previously linked to Parkinsons and our results show that the PD astrocytes manifest these known metabolic alterations.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…6A,B). Altered polyamine 23 and phospholipids 24 levels have been previously linked to Parkinsons and our results show that the PD astrocytes manifest these known metabolic alterations.…”
Section: Resultssupporting
confidence: 73%
“…6 A,B). Altered polyamine 23 and phospholipids 24 levels have been previously linked to Parkinsons and our results show that the PD astrocytes manifest these known metabolic alterations.
Figure 6 Non-targeted metabolite profiling of astrocytes revelaled several statistically significantly differentiating compounds in cell lysates ( A ) and media ( B ) of healthy and PD astrocytes analyzed by UHPLC-QTOF-MS.
…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…On the contrary, the increased levels of cadaverine match well with an overgrown Escherichia population; the bacteria in the human gut that can produce this biogenic amine [ 58 ]. It has been suggested that dysregulation of cadaverine can be involved in neurodegeneration and the formation of Lewy bodies in PD [ 59 , 60 ]. In vitro studies highlighted that biogenic amines can bind the N-terminal region of the amyloid beta peptide, significantly increasing the aggregation of α-synuclein [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease is a progressiv e disorder characterized by various motor-related symptoms, including slow movements, body tremors, and rigidity [131,132]. In general, motor symptoms related to PD irst manifest after the death of over 60% of dopaminergic neurons within the brain [133,134]. Indeed, the pathological hallmarks of PD include the generation of Lewy bodies and the erosion of dopaminergic neurons in the substantia nigra pars compacta [135][136][137].…”
Section: Parkinson's Diseasementioning
confidence: 99%